Shredding paper : the rise and fall of Maine's mighty paper industry - Hillard, Michael G. (Ithaca : ILR Press, 2021)
From the early twentieth century until the 1960s, Maine led the nation in paper production. The state could have earned a reputation as the Detroit of paper production, however, the industry eventually slid toward failure. What happened? 'Shredding Paper' unwraps the changing US political economy since 1960, uncovers how the paper industry defined and interacted with labor relations, and peels away the layers of history that encompassed the rise and fall of Maine's mighty paper industry. Michael G. Hillard deconstructs the paper industry's unusual technological and economic histories.
Previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 7, 2021).
Keywords: Paper industry -- Maine -- History -- 20th century; Paper industry workers -- Maine -- Economic conditions -- 20th century; Paper industry workers -- Labor unions -- Maine; Strikes and lockouts -- Paper industry -- Maine; Industry; US Northeast; History of the Americas; Central / national / federal government policies; Labour economics; Industry & industrial studies